Satisfying basic psychological needs through a recreational sports programme for people with intellectual disability: human growth and adapted sport in focus - Crespo-Eguílaz, Nerea; Gambra, Leyre; Varela, Apolinar; Fraguela-Vale, Raúl (Frontiers in Psychology, 2024)
Introduction Self-determination theory (SDT) highlights the importance of satisfying people’s basic psychological needs (BPN) (autonomy, competence and relatedness) in order to ensure their personal growth and wellbeing. In this regard, sport and physical activity (PA) have been shown to offer significant health benefits, particularly in the case of people with intellectual disability (ID), among whom the benefits are even more noticeable owing to their low levels of PA, sedentary lifestyle, limited opportunities to exercise, and consequently lower quality of life. The aim of this study is to assess the impact of the Más Que Tenis (“More Than Just Tennis”) inclusive recreational sports programme on the satisfaction of BPN among athletes with ID, taking into account factors such as age, gender and type of activity. Methods The sample for the study comprised 50 athletes (68% male) with ID (IQ: X = 54.33; sd = 13.43), aged 17–54 years. Data were collected using the Spanish version of the Basic Psychological Needs in Exercise Scale (BPNES), Kaufman Brief Intelligence Test (K-BIT), Satisfaction With Life Scale (SWLS), multidimensional AF5 self-concept scale, Vineland-3 Scale, and MABC-2 observation checklist. Results High levels of satisfaction of all three BPN, with autonomy scoring lowest of the three. Gender was found to be a significant predictor, with men scoring higher in all BNP. Participants reported positive perceptions in relation to physical self-concept and satisfaction with life. In terms of adaptive behaviour, deficits were detected in relation to communication and daily living skills, but not in relation to interpersonal skills. With respect to motor behaviour, satisfaction of BPN was found to correlate more with dynamic environments than with static ones. The findings indicate the effectiveness of the Más Que Tenis programme in satisfying the BPN of people with ID. Participants reported improved physical skills, competence, social integration and interpersonal relations, though also insufficient autonomy in relation to choosing what exercises to do. Conclusion Satisfaction of BPN through the programme was found to correlate positively with athletes’ satisfaction with life and adaptive development, leading to improved personal and neuropsychological wellbeing.